Biografi poststrukturalis Effendi seniman Sukuraga Kota Sukabumi Jawa Barat 1962-2022 - Rizky, Eva Nikmatul (Universitas Negeri Malang, 2024)
Abstract Effendi, who is often called Kang Fendi Sukuraga, was born in Sukabumi on April 16, 1958. Moving from one region to another helped in improving Effendi’s social habitus development. Start from living at his grandfather’s house in Jakarta, followed his Uncle to Semarang, lived in Yogyakarta and Bali to study art. Finally, he decided to settle down in his hometown at Sukabumi City. His disposition of a hard work habit makes him keep trying and never give up even when he faces difficulties. The aims of this study were to know and understand the process by which Effendi can become a successful Sukuraga artist. This study used a historical method (heuristic, criticism, interpretation, and historiography). The results of this study were Effendi’s journey in achieving success was obtained by going through various obstacles and problems: from parents who were against Effendi going to art school, Effendi dropped out from technical school and fled to Jakarta, then followed his Uncle to Semarang, became a busker in Semarang and Yogyakarta, until he had to switch between SSRI.Abstrak Effendi atau yang kerap dipanggil Kang Fendi Sukuraga lahir di Sukabumi pada 16 April 1958. Pindah dari satu wilayah ke wilayah lain, mematangkan habitus sosial Effendi. Dimulai dari tinggal di rumah Kakeknya di Jakarta, ikut Paman ke Semarang, tinggal di Yogyakarta hingga Bali untuk bersekolah seni. Hingga pada akhirnya ia memutuskan untuk menetap di kampung halamannya di Sukabumi. Disposisi pekerja keras sebagai habitus membuatnya terus berusaha dan pantang menyerah meski ditimpa kesulitan. Tujuan dari penelitian ini yaitu mengetahui dan memahami proses Effendi bisa sukses menjadi seniman Sukuraga. Metode penelitian yang digunakan adalah metode penelitian sejarah (heuristik, kritik, interpretasi, dan historiografi). Hasil dari penelitian ini adalah perjalanan Effendi dalam meraih kesuksesan diperoleh dengan melewati berbagai rintangan dan permasalahan: dari orang tua yang menentang Effendi bersekolah seni, Effendi putus sekolah teknik dan kabur ke Jakarta, lalu ikut Paman ke Semarang, menjadi pengamen di Semarang dan Yogyakarta, hingga ia harus berpindah-pindah SSRI.